2017
DOI: 10.22606/epp.2017.22003
|View full text |Cite
|
Sign up to set email alerts
|

Distribution of Nutrients in the Soils of a Unique Tropical Agroecosystem

Abstract: Kuttanad agroecosystem, once the rice bowl of Kerala, is facing a serious threat from human activities. The present study assessed the nutrient status of Kuttanad paddy soils and the spatial distribution of Nutrients using GIS technique. 117 soil samples were collected from the six agroecological zones of Kuttanad. Out of the 117, 92 were from paddy fields and 25 were from canals. The soil samples were analyzed for pH, organic Carbon (%), available nitrogen (kg/ha), available phosphorous (kg/ha) and available … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
1
1

Year Published

2021
2021
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 9 publications
3
1
1
Order By: Relevance
“…Despite this, the soils showed an available N content ranging from 275.70-502.95 kg h -1 which remained below the higher N availability class (>560 kg h -1 ). This contrasts the finding of Thafna et al (2017) who observed a high N content (771.91 kg h -1 ) in Kuttnad soils. This is possibly due to an increased utilization of N by the previous crop (Guo et al, 2017).…”
Section: Soil Nutrient Statuscontrasting
confidence: 99%
See 3 more Smart Citations
“…Despite this, the soils showed an available N content ranging from 275.70-502.95 kg h -1 which remained below the higher N availability class (>560 kg h -1 ). This contrasts the finding of Thafna et al (2017) who observed a high N content (771.91 kg h -1 ) in Kuttnad soils. This is possibly due to an increased utilization of N by the previous crop (Guo et al, 2017).…”
Section: Soil Nutrient Statuscontrasting
confidence: 99%
“…The available K content of the soils ranged from 46.50-383.20 kg h -1 which is in agreement with the earlier finding of Thafna et al (2017) that the soils in this region had a high content of K. The increase in soil organic matter (Thafna et al, 2017), soil texture and irrigation regime are some of the reasons reported for the increase in K content in soil.…”
Section: Soil Nutrient Statussupporting
confidence: 90%
See 2 more Smart Citations
“…Adv Agri Food Res J 2021; 2(2): a0000232. https://doi.org/10.36877/aafrj.a0000232 areas and less fertiliser application in low nutrient field zones (Thafna et al, 2017;Whetton et al, 2017). This uniform fertiliser management under spatially variable conditions can cause crop nutrient deficiencies as well as increases the in input cost due to over fertiliser application.…”
Section: Introductionmentioning
confidence: 99%